Analysis of Circadian Rhytme Variations on Glucose Examination Results - Rahmani, Putri Ziddanur; Jiwintarum, Yunan; Tatontos, Erlin Yustin; Pauzi, Iswari (Balai Publikasi Indonesia, 2024)
Background: Circadian rhythm is a term used to describe the 24-hour physiological rhythm of organisms. According to Minister of Health Regulation no. 43 of 2013 concerning How to Organize a Good Clinical Laboratory, the Circadian rhythm variation is explained in the body as levels of certain substances change from time to time. Changes in substance levels that are influenced by time can be cyclical, such as daily cycles (diurnal variations), monthly cycles (menstruation), or linear/straight lines, such as age. Classic experiments using a 72-hour glucose clamp methodology, demonstrated that humans exhibit a robust Circadian rhythm in insulin secretion, independent of food and glycemia. Additionally, a cell-autonomous Circadian clock appears to oversee the diurnal rhythm in glucose-induced insulin secretion.Research Objectives: Knowing the analysis of Circadian rhythm variations on glucose examination results. Research Methods: Analytical observational analysis using cross sectional methods and purposive sampling techniques. The sample population of applied TLM undergraduate students class of 2020 had blood serum taken and using the Slovin formula to determine the sample size, 36 samples were obtained with respondents without a history of diabetes mellitus. Data analysis used the Paired t-test statistical test. Research Result: The results obtained from the examination of the average glucose level at the time of sampling in the morning were 80.25 mg/dl, in the afternoon 96.5 mg/dl, and in the evening 85.91 mg/dl. The results of the paired t-test statistical analysis obtained Sig. (2-tailed) or p 0.010 means p < 0.05 there is a difference in the average glucose results at the time of sampling in the morning and afternoon and Sig. (2-tailed) or p 0.115 means p > 0.05 there is no difference in the average glucose test results at the time of sampling in the morning and evening. Conclusion: Blood glucose levels taken in the morning have lower average levels than during the day and evening.